Does Law (D)evolve? - Marquet, Clément (Revue québécoise de droit international / Quebec Journal of International Law / Revista quebequense de derecho internacional, 2025)
The article pays tribute to Gabrielle Marceau’s vision of law as a tool for social progress, while examining the opposite dynamic: the regression of international law. It begins by distinguishing between the words “evolve” and “devolve,” showing how erosion can take institutional and linguistic forms. Institutional erosion is illustrated by the paralysis of the World Trade Organisation (WTO) Appellate Body and attacks on the International Criminal Court (ICC), both of which undermine multilateral dispute settlement and justice. Language erosion is explored through two strands: active efforts to dilute legal standards, as seen in humanitarian law debates on cyber operations or in the United Nations Security Council negotiations, and passive erosion, where permissive interpretations of the right to self-defence gradually reshape the norm. The article highlights how these erosions may be driven by states that feel international law no longer serves their political interests, though they carry the risk of fragmentation and unpredictability. At the same time, it notes forms of resistance and adaptation, such as the WTO’s Multi-Party Interim Appeal Arrangement, the Kampala Amendments on the Crime of Aggression to the Rome Statute of the ICC, and initiatives by states to defend humanitarian law. The overall argument is that vigilance and proactive engagement are needed to ensure that international law’s flexibility, central to Gabrielle Marceau’s legacy, continues to serve justice and humanity rather than regression.